Crystalline boron-linked tetraaminoethylene radical cations - Su, Yuanting (2018)
Single-electron oxidation of neutral boryl-linked tetraaminoethylene derivatives 4 led to the formation of radical cations 4˙+, which have been isolated and fully characterized. X-ray diffraction analysis, EPR spectroscopy, and computational studies revealed that the unpaired electron is delocalized over the B2N4C2 skeleton and the spin density mainly resides on the carbon and boron atoms.